2018
DOI: 10.1038/s41426-018-0058-5
|View full text |Cite
|
Sign up to set email alerts
|

Ranavirus genotypes in the Netherlands and their potential association with virulence in water frogs ( Pelophylax spp.)

Abstract: Ranaviruses are pathogenic viruses for poikilothermic vertebrates worldwide. The identification of a common midwife toad virus (CMTV) associated with massive die-offs in water frogs (Pelophylax spp.) in the Netherlands has increased awareness for emerging viruses in amphibians in the country. Complete genome sequencing of 13 ranavirus isolates collected from ten different sites in the period 2011–2016 revealed three CMTV groups present in distinct geographical areas in the Netherlands. Phylogenetic analysis sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 55 publications
2
16
0
2
Order By: Relevance
“…Recent efforts to sequence complete ranavirus genomes associated with epizootics in ranaculture revealed the presence of CMTV-like viruses in captive bullfrogs and also CMTV ϫ FV3 recombinants. CMTV-like and FV3-like ranaviruses are associated with wild amphibian mortalities in Europe (14,15), but CMTV has never been reported in wild amphibians in North America. One study (11) reported a CMTV ϫ FV3 recombinant (Rana catesbeiana virus-Z [RCV-Z2]) in a commercial frog farm in the United States, and this isolate is twice as virulent as wild-type FV3 (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent efforts to sequence complete ranavirus genomes associated with epizootics in ranaculture revealed the presence of CMTV-like viruses in captive bullfrogs and also CMTV ϫ FV3 recombinants. CMTV-like and FV3-like ranaviruses are associated with wild amphibian mortalities in Europe (14,15), but CMTV has never been reported in wild amphibians in North America. One study (11) reported a CMTV ϫ FV3 recombinant (Rana catesbeiana virus-Z [RCV-Z2]) in a commercial frog farm in the United States, and this isolate is twice as virulent as wild-type FV3 (13).…”
mentioning
confidence: 99%
“…Ranavirus research has primarily focused on describing viruses isolated from captive and commercial facilities, but few studies have reported lineages and levels of genetic diversity in viral populations isolated from wild amphibians. In Europe, studies revealed the presence of different FV3-like and CMTV-like lineages from mass mortalities in Spain, the United Kingdom, and the Netherlands (14,15,(17)(18)(19). In North America, a previous study (8) sequenced two genes from ranaviruses described in Canada and found putative recombinant viruses in southern Canada and a new FV3-like lineage from northern Canada (i.e., Wood Buffalo ranavirus [WBRV]).…”
mentioning
confidence: 99%
“…but some common newts (L. vulgaris; Kik et al, 2011). Subsequent investigations into amphibian morbidity and mortality events in the Netherlands has revealed that the CMTV-like Ranavirus is spreading and is the causative agent of many of the observed events (Rijks et al, 2016;Spitzen-van der Sluijs et al, 2016b;Saucedo et al, 2018). It is also important to note that these outbreaks of disease are affecting the common spadefoot (P. fuscus), which is a threatened species (Spitzen-van der Sluijs et al, 2016c).…”
Section: Ranavirusesmentioning
confidence: 99%
“…Imagem 39 -Histopatologia em rã da espécie Lithobates catesbeianus infectada com Ranavirus. Ranavirus infectando anfíbios parece não funcionar com tilápias do Nilo.Em um trabalho recente, analisando rãs do gênero Pelophylax,Saucedo et al (2018) não encontraram positividade para Ranavirus através das técnicas de PCR e IHC, apesar dos animais analisados apresentarem vários sinais de infecção pelo vírus, incluindo a presença de corpúsculos de inclusão citoplasmáticos e necrose em diferentes tecidos. Nesse estudo, 13 isolados de Ranavirus, coletados de dez diferentes regiões na Holanda, tiveram o genoma sequenciado, sendo identificados perfis genômicos de três diferentes grupos de CMTV-like presentes em áreas distintas do país.A técnica de ISH é utilizada para a identificação de presença viral em tecido infectado, com o emprego de sondas moleculares que localizam sequências específicas de ácido nucléico dentro de seções de tecido fixas(MILLER et al, 2015).…”
unclassified
“…O BIV foi a espécie viral causadora de surto epizoótico com mortalidade de 100% de tilápias em cativeiro da espécie Oreochromis mossambicus, dentro de um período de 60 dias na Austrália, reportado por Ariel e Owens (1997). Semelhante a este trabalho, outros trabalhos recentes também demonstraram a inserção dos BIV no clado dos FV3, como por exemplo o trabalho deSaucedo et al (2018). espécies dentro do mesmo gênero.…”
unclassified